2020
DOI: 10.9758/cpn.2020.18.2.270
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Levels of Serum 100 Beta Protein, Neuron-specific Enolase, Tau, Active Caspase-3, M30 and M65 in Children with Autism Spectrum Disorders

Abstract: Objective: The purpose of this study was therefore to investigate whether neuronal, axonal, and glial cell markers (Neuron-specific enolase [NSE], tau, serum 100 beta protein [S100B], respectively) and apoptosis markers (active caspase 3, M30, M65) and whether these parameters can be used as diagnostic biomarkers in autism spectrum disorders (ASD). Methods: This study measured the serum S100B, NSE, tau, active caspase 3, M30, and M65 levels in 43 patients with ASD (aged 3−12 years) and in 41 age-and sex-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 54 publications
2
24
0
2
Order By: Relevance
“…Novel and more recent studies revealed changes in Tau protein expression in autistic patients suggest the importance of dyshomeostasis of this protein in the aetiology of ASD [ 28 , 41 , 42 ]. There are indications that suggest that “Alzheimer’s protein” may turn up as a potential target for autism treatments after that in murine models of ASD a genetic reduction in Tau levels eases the symptoms typical for autism [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel and more recent studies revealed changes in Tau protein expression in autistic patients suggest the importance of dyshomeostasis of this protein in the aetiology of ASD [ 28 , 41 , 42 ]. There are indications that suggest that “Alzheimer’s protein” may turn up as a potential target for autism treatments after that in murine models of ASD a genetic reduction in Tau levels eases the symptoms typical for autism [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the key proteins responsible for the stabilization and regulation of the MTs network is Tau (tubulin-associated unit), which is mainly found in the axonal compartment [ 27 ]. Therefore, Tau plays a particularly important role in the stabilization of axonal MTs thus enables axonal transport of signal molecules and trophic factors as well as participates in the processes of neurite growth and synaptogenesis [ 28 , 29 ]. The affinity of Tau for the MTs depends on its phosphorylation state [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were published from 2012 to 2019 (Abou-Donia et al 2019 ; Al-Ayadhi and Mostafa 2012 ; Ayaydin and Kirmit 2020 ; Esnafoglu et al 2017 ; Guloksuz et al 2017 ; Ma et al 2019 ; Peng and Zhu 2017 ; Shaker et al 2016 ; Tomova et al 2019 ; Zhou 2015 ) (Table 1 ). Ten studies encompassed 822 participants and 451 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies encompassed 822 participants and 451 cases. Three studies were performed in China(Ma et al 2019;Peng and Zhu 2017;Zhou 2015), three in Turkey(Ayaydin and Kirmit 2020;Esnafoglu et al 2017;Guloksuz et al 2017), one in the USA (Abou-Donia et al 2019), one in Saudi Arabia (Al-Ayadhi and Mostafa 2012), one in…”
mentioning
confidence: 99%